The determinants of outward foreign direct investment from Latin America and the Caribbean: An integrated entropy-based TOPSIS multiple regression analysis framework - Henrique Correa da Cunha; Vikkram Singh; Shengkun Xie (Journal of Risk and Financial Management, 2022)
Given that home country factors play a major role in the internationalization of emerging market firms, there is an ever-growing debate on how they influence the intensity of outward foreign direct investment (OFDI) from these regions. This study investigates how home country factors affect the OFDI intensity in Latin America and Caribbean (LAC) countries. We use the entropy weight method, which uses the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method and a balanced panel data consisting of 19 countries from 2007 to 2016. The results show a positive association between macroeconomic performance, formal institutions, infrastructure, technology and the OFDI intensity. Furthermore, we find that robust formal institutions, along with the quality of infrastructure and technology, positively moderate the relationship between macroeconomic performance and the OFDI intensity. These findings show that the internationalization of LAC firms is highly dependent on the contextual conditions in their markets.
Keywords: 330; OFDI; IFDI; home country context; formal institutions; infrastructure and technology; macroeconomic performance; TOPSIS; entropy weight method; Latin America and the Caribbean